Utilización de aceite residual de cocina producido por los bares de la Universidad Nacional de Chimborazo para la elaboración de jabón líquido - Calderón Villamarin, Christopher Alexander (2019)
The residual cooking oil is a byproduct of great environmental impact as it is not disposed of properly due to the degrading thermal processes to which it is subjected, it is necessary to generate an alternative for its reuse, so the present work proposes the base liquid treatment of residual oil produced by the bars of the National University of Chimborazo, the use of experimental methodology, based on the Statistical Package for Social Sciences (SPSS) and INFOSTAT version 6.2; Analyzing and comparing the results obtained with the quality parameters established by the INEN 2421 standard of physical and chemical requirements for cooking oil, after the quality analysis of raw material (residual oil) this was used for the production of solid soap (base ), to be addicted to liquid soap by modification. Respect liquid soap verify stability determinations to determine its useful life time using the protocols cited by the INEN 850 standard, presenting the following average results: pH 5.9955, free alkalinity of 0.1101%, acidity 0.2307% , 1.4231% saponifiable matter, 0.6410% chlorides, in addition to physical determinations using and comparing with the results obtained by the protocols of other authors regarding: viscosity, fat drag and moisture, where average values of 16 were obtained, 3952%, 99.4474% and 75.6571% respectively, the viscosity determination being the analysis with the highest standard deviation with a value of 13, 9370%.